SOME REMARKS ON THE SCOTTISH INDEPENDENCE - Marinkás, György (European Integration Studies, 2017)
Some authors claim that we are witnessing the twilight of nation states, which are eroded by two major forces: firstly the ever growing number and power of supranational organizations and secondly the spread of minority-regionalism. The latter could easily render nation states fragmented and insignificant, that’s why the author finds it important to examine this phenomenon through the scope of the Scottish and Catalonian aspirations for independence. Both groups are so called “captive nations” or “substate nations”: they are culturally distinct groups living on their traditional territory, who think of themselves as distinct people or a distinct nation, and show a deep attachment to their cultural distinctiveness and to their homeland, which they have struggled to maintain despite being incorporated (often involuntarily) into a larger state.